2023
DOI: 10.3390/coatings13091581
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cr-Al-Si-N and DLC-Si Thin Coatings on Wear Resistance of Titanium Alloy Samples with Different Surface Conditions

Marina A. Volosova,
Maxim A. Lyakhovetsky,
Artem P. Mitrofanov
et al.

Abstract: The influence of Cr-Al-Si-N, DLC-Si, and Cr-Al-Si-N/DLC-Si thin coatings deposited on titanium alloy (Ti-Al-Zr-Sn-Nb system) samples with different surface reliefs on wear resistance under abrasion and fretting conditions was investigated. The influence of coatings on the initial microrelief after finishing milling and lapping with micro-grained abrasive was studied by profilometry. The Martens hardness (H) and the elastic modulus (E) were determined through nanoindentation. The H/E ratio was 0.08, 0.09, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…At the same time, as preliminary experiments and analysis of literature data [30,31] have shown, in the conditions of semi-finishing cutting, the defining element of tool wear is the wear chamfer on its rear surface. The analysis of the back surface wear profile performed in the study [14,28,31] showed that the lowest variability of the wear measurement results is characterized by the average back surface wear along the leading cutting edge. This parameter at constant values of the front and back angles of the cutting wedge reflects the dimensional wear resistance of the tool.…”
Section: Experimental Results and Their Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, as preliminary experiments and analysis of literature data [30,31] have shown, in the conditions of semi-finishing cutting, the defining element of tool wear is the wear chamfer on its rear surface. The analysis of the back surface wear profile performed in the study [14,28,31] showed that the lowest variability of the wear measurement results is characterized by the average back surface wear along the leading cutting edge. This parameter at constant values of the front and back angles of the cutting wedge reflects the dimensional wear resistance of the tool.…”
Section: Experimental Results and Their Discussionmentioning
confidence: 99%
“…The above properties determine the wear resistance of the cutting tool, i.e., the ability to resist the removal of its particles during contact interaction. Along with the requirements for the physical-mechanical and thermophysical properties of the tool material, a necessary condition for achieving sufficiently high cutting properties of the tool is a low physical and chemical activity of the tool material to the processed material, which is achieved by applying coatings [25][26][27][28].…”
Section: 𝑇 𝑙 𝑉mentioning
confidence: 99%
See 1 more Smart Citation